Involvement of sulfates from cruzipain, a major antigen of Trypanosoma cruzi, in the interaction with immunomodulatory molecule Siglec-E - Ferrero, Maximiliano R (2016)
Fil: Ferrero, Maximiliano R. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Parasitología. Departamento de Investigación y Docencia; Argentina.